COMPARISONAL ANALYSIS OF LEVELS OF LEAD (Pb) IN FLYINGFISH (Decapterus sp) FOR SALE IN KAIRATU MARKET AND TRADITIONAL MARKET AT MARDIKA AMBON WITH SSA METHOD - Cut Bidara Panita Umar; Amelia Nilwele; Neneng Ita Temmar (Jurnal Medika Husada, 2022)
Lead is one of the non-essential heavy metals which is very dangerous and inhibits the activity of enzymes involved in the formation of hemoglobin (Hb) and a small part of lead (Pb) is excreted in the urine or feces because some of it is bound by protein, while the rest accumulates in the kidneys, liver, nails, adipose tissue, and hair. Fish are aquatic organisms that can move quickly. Fish in general have the ability to avoid the effects of water pollution. If the body of the fish contains high levels of heavy metals and exceeds the normal limits that have been determined, it indicates that environmental pollution has occurred. The purpose of this study was to determine the levels of lead in flying fish (Decapterus sp) which are sold in the Kairatu market and the Ambon Mardika market. The research design is atomic absorption spectrophotometry (AAS). The results of the analysis of lead (Pb) levels in flying fish which are traded in the Kairatu market and the Ambon mardika market in the morning, it can be concluded as follows: From the two samples studied, the samples did not get Pb levels that the samples were below the threshold, namely ≤ 0.25 ppm